Severe fibrosis of the pancreas in chronic pancreatitis: main pathological components, immunophenotype of fibrogenic cells and collagen - V. О. Tumanskiy; I. S. Kovalenko (Zaporozhye State Medical University, 2013)
Pathomorphological feature of chronic pancreatitis (CP) is the development of pancreatic fibrosis with the accumulation of various collagen types, tubulin, fibronectin, laminin, and also intermediate filament proteins produced by activated pancreatic stellate cells (PSCs), which express the cytoskeletal α-smooth muscle actin (α-SMA). The aim of the research: determination of immunophenotype and proliferative activity of pancreatic stellate cells as well as the main histotopographic components of severe pancreatic fibrosis and accumulation of collagen I, III and IV types in pancreas at CP. Materials and methods. Histological, histochemical (Van Gieson's and Masson's trichrome staining), immunohistochemical (α-SMA, vimentin, desmin, fibronectin, Ki-67, collagen I, III and IV types) and morphometric studies (Image J program) of accumulation of various collagen types, represented in standard unit of optical density (SUOD), were held at pancreas biopsies of 30 patients (35-72 years old) with CP. Results. It was found that development of severe pancreatic fibrosis is promoted by proliferation and increase of α-SMA+, vimentin+, desmin+ activated stellate cells and deposition of significant amount of collagen I, III, IV types and fibronectin in pancreas that are synthesized by PSCs. In areas of severe fibrosis Ki-67 expression is detected in the nuclei of at least 25% of PSCs, that corresponds to relatively low levels of proliferation. Four components of severe pancreatic fibrosis: circular-periductal fibrosis involving the large ducts of the pancreas, laminar fibrosis in extensive fibrous fields between large ducts and acinar tissue, as well as tape-like interlobular and septal-periacinar intralobular pancreatic fibrosis are identified in patients with CP. Conclusion. Morphological manifestation of severe circular-periductal pancreatic fibrosis is the presence of significant concentric fibrosis around the large ducts with atrophy and replaceable fibrosis of acinar tissue around the ducts, and the presence of inflammatory cell infiltration in fibrous areas. A large number of α-SMA-positive PSCs, and significant deposition of collagen are revealed in the wall of the large ducts and in the area of periductal fibrosis: according to morphometric data the area of accumulation of type I collagen was 24,09 ± 0,92 SUOD, type III collagen - 33.21 ± 1,24 SUOD, type IV collagen - 17,78 ± 0,84 SUOD. Pathomorphological signs of severe laminar fibrosis are extensive fibrous fields between large ducts and pancreatic acinar tissue containing large amount of α-SMA-positive stellate cells and collagen depositions. According to morphometric data area of collagen type I accumulation in the fields of laminar fibrosis was 24,09 ± 0,72 SUOD, type III collagen - 22,68 ± 0,54 SUOD, type IV collagen - 15,34 ± 1,15 SUOD. Morphological manifestations of severe pancreatic interlobular and intralobular fibrosis are diffused tape-like interlobular fibrosis, involving the most lobules, as well as septal-periacinar intralobular fibrosis with acinar atrophy and reorganization of pancreatic lobules. These zones show increased number of activated α-SMA-positive PSCs and significant deposition of collagen. According to morphometric data accumulation of type I collagen was 20,48 ± 0,98 SUOD, type III collagen - 25,04 ± 0,71 SUOD, type IV collagen - 18,70 ± 0,86 SUOD in these zones.